Radical Reform: Islamic Ethics and Liberation by Tariq Ramadan (Oxford: Oxford University Press, 2009. 372 pages.) (American Journal of Islam and Society, 2009)
Tariq Ramadan’s latest book, Radical Reform: Islamic Ethics and Liberation,consists of sixteen chapters divided into four major sections: “OnReform,” “ClassicalApproaches of the Fundamentals of Law and Jurisprudence,”“For a New Geography of the Sources of Law and Jurisprudence,”and “Case Studies.”The author commences by criticizing the process of ijtihad as it currentlyexists. Although it made things progress for centuries, he finds thatijtihad is highly inadequate, has not resolved the crises faced by Muslims,and has not produced the expected renewal. As far as taqlid is concerned,Ramadan argues that imitating past scholars makes Muslims believe thatthey can avoid today’s challenges by taking refuge in the past. Ijtihad, hebelieves, has always been behind the times, simply seeking to interpretIslamic law in light of new changes and developments in society. He is criticalof literalist, traditionalist, conservative, and culturally based interpretationsof Islam. Arab culture, he points out, is not Islam’s sole culture. Thusif Islam is truly a universal religion, it must provide its followers with themeans to approach cultural diversity.The author provides an intelligent criticism of Salafism, which confuseseternal principals with historical models and thereby reduces Islam’s universalityto the dream of an impossible return to the past and an irresponsible“nostalgia of origins.”As he points out, many Salafi reductionists cannot distinguishbetween religion and culture and therefore view diversity and socioculturalevolution as religious innovations. Not only is he critical of mosttraditional approaches to ijtihad, he is critical of virtually every Islamicmovement when it comes to their methods of implementing Islamic law ...